Coagulation assessment with the new generation of oral anticoagulants. Issue 6 (18th May 2015) - Pollack, Charles V
Abstract : Long-term oral anticoagulant (OAC) therapy is used for the treatment and prevention of thrombosis and thromboembolism. As OAC use is so widespread, emergency physicians are likely to encounter patients on anticoagulant therapy in the emergency department (ED) on a regular basis, either for the same reasons as the population in general or as a result of the increased bleeding risk that OAC use entails. The vitamin K antagonist warfarin has been the standard OAC for several decades, but recently, the newer agents dabigatran etexilate, rivaroxaban and apixaban (collectively, novel OACs, non-vitamin K OACs, or simply 'NOACs') have become available for long-term use. Protocols for assessing and managing warfarin-treated patients in the ED are well established and include international normalised ratio (INR) testing, which helps guide patient management. However, the INR does not give an accurate evaluation of coagulation status with NOACs, and alternative tests are therefore needed for use in emergency settings. This paper discusses what information the INR provides for a patient taking warfarin and which coagulation tests can guide the physician when treating patients on one of the NOACs, as well as other differences in emergency anticoagulation management.